Problems of empiricism: Philosophical papers: Volume 2 - Feyerabend, Paul (New York Cambridge University Press, 1981)
Over the past thirty years Paul Feyerabend has developed an extremely distinctive and influentical approach to problems in the philosophy of science. The most important and seminal of his published essays are collected here in two volumes, with new introductions to provide an overview and historical perspective on the discussions of each part. Volume 1 presents papers on the interpretation of scientific theories, together with papers applying the views developed to particular problems in philosophy and physics. The essays in volume 2 examine the origin and history of an abstract rationalism, as well as its consequences for the philosophy of science and methods of scientific research. Professor Feyerabend argues with great force and imagination for a comprehensive and opportunistic pluralism. In doing so he draws on extensive knowledge of scientific history and practice, and he is alert always to the wider philosophical, practical and political implications of conflicting views. These two volumes fully display the variety of his ideas, and confirm the originality and significance of his work.